Formulation, Optimization, and Evaluation of Bioadhesive Xanthan Gum Based Buccal Patch for Sustained Delivery of Ropinirole Hydrochloride - Kayande, Kalyani (Asian Journal of Pharmaceutics (AJP), 2021)
Introduction: Parkinson’s disease is a neurological disorder in which there is a gradual loss of brain cells that make and store dopamine. Ropinirole hydrochloride (ROPH) is an anti-Parkinson’s drug which undergoes extensively first-pass metabolism, with oral bioavailability 45%. Aim: The study aimed to formulation, optimization, and evaluation of ROPH buccal patch using xanthan gum (XG). Materials and Methods: Solvent casting method was used to prepare mucoadhesive buccal patch ROPH using XG as a mucoadhesive polymer, polyvinylpyrrolidone K90 as a film former and polycarbophil and hydroxypropyl methylcellulose K4M as a release retardant. Results and Discussion: The dissolution studies showed sustained release of drug about 97.86% for 8 h following Korsmeyer-Peppas model (r2=0.989, n = 0.199). The optimization of all prepared batches was carried out by 32 factorial designs, the optimized batch F3 showed acceptable physicochemical properties and having swelling index 286.10%, mucoadhesive strength 26.90 g, tensile strength 0.04±0.01 N/mm2, and in vitro drug release 97.86%. Ex vivo permeability was carried out using sheep buccal mucosa and it was found to be increased by five folds than that of formulation without penetration enhancer. After histopathological evaluation cellular membrane was found to be intact and did not show any signs of necrosis. Conclusion: Thus, an attempt to formulate a stable mucoadhesive buccal patch was made. The in vitro studies have shown that this is a potential drug delivery system for ROPH with good stability and release profile.